2021
DOI: 10.1007/s11005-020-01350-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the spectral gap for the Landau–Pekar equations

Abstract: The Landau–Pekar equations describe the dynamics of a strongly coupled polaron. Here, we provide a class of initial data for which the associated effective Hamiltonian has a uniform spectral gap for all times. For such initial data, this allows us to extend the results on the adiabatic theorem for the Landau–Pekar equations and their derivation from the Fröhlich model obtained in previous works to larger times.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Further improvements have been obtained for confined polarons or polaron models with more regular interaction [13,16,43]. For completeness, let us also mention recent progress in the understanding of the polaron path measure [3,42] as well as the increased interest in the analysis of the Schrödinger time evolution of strongly coupled polarons [11,14,15,23,30,31,38].…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Further improvements have been obtained for confined polarons or polaron models with more regular interaction [13,16,43]. For completeness, let us also mention recent progress in the understanding of the polaron path measure [3,42] as well as the increased interest in the analysis of the Schrödinger time evolution of strongly coupled polarons [11,14,15,23,30,31,38].…”
Section: The Modelmentioning
confidence: 99%
“…for all v ∈ L 2 (R 3 ) with v|∇ϕ L 2 = 0 (note that this also implies (iii)). For that purpose we quote [11,Lemma 2.7] stating that there exists a constant τ > 0 such that…”
Section: Y) (3232)mentioning
confidence: 99%
“…In [23] the Nelson model with ultraviolet cutoff has been studied in a limit of many weakly interacting fermions. The classical behavior of quantum fields has also been proven in different scaling regimes [3,5,6,7,8,9,12,13,14,16,17,19,21,26,28,34]. We also would like to mention [32] which derives the Maxwell-Schrödinger equations in a nonrigorous manner by neglecting certain terms in the Pauli-Fierz Hamiltonian.…”
Section: I3 Scaling Regimementioning
confidence: 99%
“…In this appendix we give further details about the unitary, defined by (19), and the derivation of the excitation Hamiltonian from (24). To this end, we closely follow [42,Chapter 4.1] and [43,Chapter 2.3].…”
Section: Proof Of the Theoremsmentioning
confidence: 99%
“…In [15,32,60] it has, moreover, been shown that the effect of the quantum field on the particles can in certain situations be approximated by a direct pair interaction. Let us also mention further works that focus on related models [37,38,40], a partial limit [9,12,13,14] and the strong coupling limit of the polaron [19,20,21,26,36,41,46].…”
Section: Introductionmentioning
confidence: 99%